Model of the Naqsabandiyah Order and Its Effect on Spiritual Intelligence - Abdullah, Luqman; Latipah, Eva; Kistoro, Hanif Cahyo Adi (Program Studi Pendidikan Agama Islam, 2021)
The alarming phenomenon of the current state of society has made experts realize that a person's success in life is not only determined by intellectual and emotional intelligence but also by spiritual Intelligence. Spiritual Intelligence refers to the Intelligence of the heart. In terms of the education of the heart, the Sufi sheikh has set an example by way of the tarekat, each of which has a different path. Therefore, this study tries to answer the problem by knowing how the Naqsyabandiyah tarekat model and its influence on spiritual Intelligence in Surau Nurul Amin, Boyolali Regency. This research is qualitative. The primary source of data is the Naqshbandiyah congregation builder and congregation. Data were collected by observation, in-depth interviews, and documentation. Test the validity of the data using source triangulation. The results showed: (1) The model of the Naqsyabandiyah tarekat in Surau Nurul Amin Boyolali were: Strategy through Dhikr, to foster calm; Method through Suluk, to practice honesty and discipline of the soul; and the techniques used are ubudiyah, alms, pilgrimage. (2) The development of the Naqsyabandiyah congregation in Surau Nurul Amin Boyolali influences spiritual Intelligence. Its influence is seen in the spiritual intelligence aspect of the tarekat congregation. The influence felt by each congregation is different; this is because it is routine or not in the practice of tarekat training. Some experienced a significant change in spiritual Intelligence; others experienced an increase in spiritual Intelligence.